Can Crohn's disease be diagnosed at laparotomy?. Issue 1 (January 1992) - Butterworth, R J; Williams, G T; Hughes, L E
Abstract : The typical macroscopic features of Crohn's disease have been well described and are widely regarded as sufficient to diagnose the disease at laparotomy. We report six patients undergoing laparotomy for symptomatic Crohn's disease, shown radiologically, who were found to have macroscopically normal small bowel despite careful examination of the bowel by an experienced surgeon. In four cases resection was deferred, but all subsequently deteriorated and required further surgery. Minor abnormalities found by balloon examination of the terminal ileum prompted resection in two further patients. Histology showed an unusually superficial distribution of inflammation, which could explain the negative findings at laparotomy. We conclude that normal laparotomy findings alone do not exclude a diagnosis of clinically important small bowel Crohn's disease. Crohn's disease should be considered in patients with persisting symptoms after negative laparotomy.